NILAI PENDIDIKAN KARAKTER TOKOH UTAMA NOVEL KETIKA TUHAN JATUH CINTA KARYA WAHYU SUJANI (KAJIAN PSIKOLOGI SASTRA) - Thessa Conayda; Sesilia Seli; Agus Wartaningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to describe and explain the educational value of the characters of the main characters of the novel When God falls in love by Wahyu Sujani and plans the implementation of the results of research on learning Indonesian. The research method used is content analysis using a literary psychology approach with a qualitative descriptive form. The source of the data in this study is a novel text, When Dewa Jatuh Cinta by Wahyu Sujani, published by Publisher DIVA Press, 443 pages thick, first print, July 2009. Data used in the form of quotations (words, phrases, sentences, or dialogues) relating to character education values. The results of the research on character education found in the main characters of the novel When God Fall in Love by Revelation Sujani include; (1) honest, (2) hard work, (3) responsible, (4) religious, (5) smart, and (6) patient. Novel When God Falling in Love by Wahyu Sujani can be used as material for learning literature in senior high schools by paying attention to several aspects, namely, curriculum, learning objectives, learning models, methods and learning media. Novel When God Fell In Love Revelation Sujani's work can be used as learning material in the K13 Curriculum. Keywords: Character Education, Psychology Study, Learning